Strong Associations Between Childhood Victimization and Community Violence in Male Forensic Mental Health Patients - Fosse, Roar; Eidhammer, Gunnar; Selmer, Lars Erik; Knutzen, Maria; Bjørkly, Stål (Frontiers in Psychiatry, 2021)
Background: Childhood abuse and neglect increase the risk of both mental disorders and violent behavior. Associations between child relational adversities and violent behavior have not been extensively investigated in forensic mental health settings. We asked whether the extent of child adversities predicts the extent of violence in the community in forensic mental health patients. Methods: We included 52 male patients at a medium security forensic mental health ward, with diagnoses of predominantly paranoid schizophrenia and other schizophrenia and psychotic disorders. Seventy-five percent had comorbid substance abuse. We extracted information on six types of child adversities based on clinicians' administrations of the Historical Clinical Risk Management 20 version 3 (HCR 20) scale and summary notes in electronic patient journals. These same sources were used to extract information on war trauma and interpersonal violence in the community. We established cumulative scales for exposure to number of types of child adversities and number of incidents of community violence. Results: Physical and emotional abuse, emotional and physical neglect, and bullying were associated with higher levels of community violence. We observed a linear, significant increase in the frequency of community violence with cumulative numbers of child adversity types. Conclusions: Cumulative exposure to child adversities may be associated with higher degrees of violence in forensic mental health patients, with the most violent patients having the most extensive exposures to adversities. An enhanced focus on child adversities in risk assessment and management of violence may be considered in forensic inpatient settings.